Gimnasia Cerebral para desarrollar la motricidad en escolares.Centro Educativo San Francisco de Asís, 2019 - Torres Pilatasig., Fátima Elizabeth (2019)
This research aims to provide information on brain gym to develop motor skills in students of the Centro Educativo “San Francisco de Asís,”2019. The theoretical framework describes the variables to support research, what Brain Gym is and its benefits, the role that the left and right hemispheres play and the skills that have been developed in each one of them, wat is the definition of motor skills and why it is vital in learning, the objective of this research is to present this new educational technique to Physical Culture teachers and encourage its use within the schools, giving information about the benefits it brings in the motor area of children. This study was carried out based on a descriptive-explanatory design, using the observation technique and as an instrument, the scale of assessment for the collection of data. It gives a favorable result of 56.36% in the development of gross motor control on the scale of excellent, and 24.54% in the development of fine motor control. This project ends with the conclusion that Brain Gym affects positively in the motor development of sub-level Initial 2 of the Centro Educativo “San Francisco de Asís”.